Motivação política das transferências voluntárias nos municípios cearenses - Recamonde, Jackeline Oliveira Nobre (2019)
This paper investigates if there is political motivation in the use of the voluntary transfers of the Union and the State of Ceará to its municipalities. In order to do so, models for panel data with fixed effect are estimated for a sample with all 184 municipalities in the State of Ceará from 2007 to 2017. In these models, the dependent variables are the revenues from voluntary transfers (current and capital). The results show that in all models, one or more coefficients of the political variables are statistically significant, namely: year of municipal election, year of government election, re-election of Mayor, election of the Mayor's successor, political alignment of the Mayor with the President or with the Governor (same party). The results show that in the years of municipal and governmental election, the volume of resources received by these municipalities through voluntary transfers is greater. The variable reelection of the Mayor also is significant and positive, indicating a possible use of the public machine by the manager to remain in power (political cycle) and the possibility of occurrence every two years and in a vicious way the eventual problem of adverse selection. The coefficients related to the municipal economic capacity, approximated by its own tax revenue, and the variables of the social structure, represented by the age of the population, show in most cases insignificant.